Guidelines for authors-English Version - NA, NA (Universidad Santo Tomás / Instituto Colombiano de Normas Técnicas y Certificación ICONTEC, 2009)
The purpose of SIGNOS “Investigación en sistemas de gestión” journal is to serve as a spread channel for thoughts, discussions and research results in topics related to quality, quality management, normalized management models and social responsibility as well as experiences related to the theories, models and management systems applicability, innovation and pertinence in private and public organizations.